Potential novel approaches to risk identification in advanced peripheral arterial disease. - Brand, Martin (My University, 2014)
Peripheral arterial disease (PAD) is a significant cause of morbidity and mortality in both economically developed and developing countries. Although the risk factors for PAD are well described, patients with PAD who develop critical lower limb ischaemia (CLI) are frequently asymptomatic prior to the development of CLI and the factors that determine outcomes in these patients are unclear. In the present thesis I therefore evaluated a number of potential novel risk approaches in patients with CLI, both for the development of CLI, as well as approaches that may better predict outcomes in CLI. Atherosclerotic disease, the major pathophysiological process responsible for PAD, is now well recognized as causing an increased large artery pulse wave velocity (PWV) and central aortic pulse pressure (PPc). However, through the presence of arterial stenoses proximal to the femoral artery, carotid-femoral PWV may be reduced in advanced PAD. I therefore aimed to determine whether in the context of increases in central aortic pulse pressure (PPc), decreases in carotid-femoral pulse wave velocity (PWV) predicts the presence of advanced PAD. Applanation tonometry and vascular ultrasound were employed to assess carotid-femoral PWV, PPc and carotid intima-media thickness (IMT) in 1030 randomly selected healthy adults from a community sample and 217 patients with CLI. With adjustments for confounders, participants with CLI had an increased carotid IMT (p<0.0001) and PPc (p<0.0001), but a markedly reduced PWV (m/sec)(CLI=4.38±3.14, Community sample=6.78±2.47, p<0.0001). PWV was strongly correlated with PPc (r=0.53, p<0.0001) in the community sample, but not in CLI (r=-0.04). A stiffness mismatch index (PPc/PWV) showed increased values in participants with CLI over the full adult age range assessed. With carotid IMT, PPc or aortic augmentation index in the same regression model, an increase in the stiffness mismatch index (PPc/PWV) was independently associated with CLI (p<0.0001) and a PPc/PWV value>upper 95% confidence interval in the community sample strongly predicted CLI (odds ratio=27.1, p<0.0001). In conclusion, in the context of an increased PPc,carotid-femoral PWV is markedly reduced in CLI. These results suggest that a stiffness mismatch index (PPc/PWV) may be a new risk marker for advanced PAD.As infection with the human immunodeficiency virus (HIV) is common in South Africa, and this is increasingly translating into cardiovascular disease including CLI, it is important to be able to detect those HIV positive patients whom will develop CLI. Although ankle-brachial index may detect PAD, more general screening tools to detect those at risk of cardiovascular events are required. In this regard, carotid IMT measurements may be useful.The extent to which human HIV is associated with increases in IMT independent of conventional cardiovascular risk factors is unclear. Hence, I evaluated whether independent of conventional risk factors, an increased carotid IMT occurs in African HIV infected patients with chronic critical limb ischemia (CLI). Carotid IMT was measured in 217 sequentially recruited patients with CLI, 25 of whom were HIV positive and in 430 randomly selected controls from a community sample. As compared to HIV negative patients with CLI, HIV positive patients were younger (49±10 vs. 64±11 years, p<0.0001) and had a markedly lower prevalence of hypertension and diabetes mellitus (p<0.0001), but a similar proportion of patients smoked (76% vs. 67%). However, as compared to patients with CLI who were HIV negative, HIV positive patients had a similar increase in carotid IMT (HIV positive=0.75±0.14 mm; HIV negative=0.79±0.14 mm; Controls=0.64±0.15, p<0.0001 versus Controls) even after adjustments for age, sex and conventional risk factors (HIV positive=0.75.±0.13 mm; HIV negative=0.73±0.15 mm, Controls=0.66±0.15, p<0.005). IMT was similarly increased in HIV positive patients with CLI as compared to HIV negative patients with CLI when assessed in men, smokers, and black African patients only (p<0.05-0.0001), or in those who were receiving highly active antiretroviral therapy (n=12, 0.74±0.10 mm) as compared to those not receiving therapy (0.75±0.15 mm). As compared to controls,the age- sex- and conventional risk factor-adjusted odds of having an IMT≥0.8 mm was similarly increased in patients with CLI who were HIV positive (odds ratio=8.89, CI=2.79-28.32, p=0.0002) as those who were HIV negative (odds ratio=2.70 CI=1.51-4.81, p<0.001).In conclusion, these results suggest that despite being of a younger age, with or without conventional risk factor adjustments, marked increases in carotid IMT in HIV is a risk factor for CLI. Thus, carotid IMT measurements may be a useful screening tool to detect those patients with HIV at risk of CLI. Although asymptomatic decreases in left ventricular (LV) ejection fraction (EF) predict long-term mortality and decreased patency of endovascular interventions in patients undergoing vascular surgery, in patients with chronic critical lower limb ischemia (CLI), the prevalence of asymptomatic decreases in EF and the characteristic features thereof are unclear. I performed echocardiography in 93 sequentially recruited patients with CLI without symptoms of heart failure and 698 randomly recruited participants from a community sample.As compared to the community sample, patients with CLI had markedly reduced multivariate adjusted EF (CLI=56±12%, Community sample=67±11%, p<0.0001), LV midwall fractional shortening (FSmid)(p<0.0001), stroke volume index (SV)(p<0.0001), cardiac output index (CO)(p<0.05), and increased total peripheral resistance index (TPR)(p<0.05). In contrast to only 1/698 community participants, 26/93 (28%) patients with CLI had an EF<40%, of which only 5 had a previous myocardial infarction; and CLI was associated with a reduced EF independent of clinical evidence of coronary artery disease (CAD) and additional confounders (odds ratio=250, p<0.0001). In patients with CLI with an EF<40%, CO, SV and FSmid were all substantially reduced (p<0.0001), pro-brain natriuretic peptide concentrations and E/A were increased (p<0.05), whilst LV end diastolic volume index was marginally increased (p<0.05) as compared to those with an EF≥55%. Pro-brain natriuretic peptide had a poor sensitivity and specificity for the detection of an EF <40%. In conclusion, CLI is associated with a high prevalence of reduced EF independent of clinical evidence of heart failure, CAD and additional confounders, the main mechanism of which is a markedly reduced myocardial systolic function. This translates into decreased CO and increased TPR, alterations that may contribute toward increased mortality or reduced patency of endovascular interventions after vascular surgery.In conclusion, the results of this thesis suggest that longitudinal studies should be conducted to evaluate whether an arterial mismatch index (PPc/PWV) can predict the development of CLI independent of alternative cardiovascular risk factors; whether carotid IMT may be used to predict those at a high risk of cardiovascular events including CLI in HIV positive patients; and whether the presence of asymptomatic low LV EF may predict outcomes after surgery for CLI. Furthermore, the results of this thesis suggest that clarity is required to identify the exact large artery changes that characterize HIV positive patients with advanced PAD in South Africa.
Keywords: Vascular Diseases--diagnosis